Pengaruh Pelatihan Medicine Ball Sit Up Throw Terhadap Kekuatan Otot Lengan dan Otot Punggung Pada Siswa Putra kelas VII SMP Negeri 4 Bolo - Taufiq Hidayat (Inspiree)
This studi aims to determine the effect of medicine ball sit-up throw training to arm muscle power and back muscle power. The research is quasi-experimentally in which the randomized pretest posttest control group design.Sample were male students SMP Negeri 4 bolo numbered people. The instrument used for research testing arm muscle power is push-up 60 second while the instrument to test the back muscle power is back and leg dynamometer.Furthermore the data analyzed by independent t-test at a significance level of less (α) of 0,05 with SPSS.16.0 Based on the results of independent t-test showed; (1) Variable arm muscle power with significance value 0,000, (2) Variable back muscle power with significance value 0,010. The significant value calculated is less than the value of a 0,05 so the hypothesis research “ Medicine ball sit -up throw effect on arm muscle power and back muscle power” accepted. It can be concluded that the training medicine ball sit-up throw significant effect on the increase in arm muscle power and back power on male students SMP Negeri 4 Bolo I the academic year of 2020/2021. For sports teacher trainers coaches and atheles are advised to use alternate training as medicine ball sit-up throw alternative way to increase arm muscle power and back muscle power.